HYBRIDIZATION OF INTERNATIONAL AND NATIONAL CURRICULA: CRITICAL REFLECTION THROUGH THE THOUGHT OF PAULO FREIRE - Ines Alifah Wachidatun Chasanah; Rhoma Dwi Aria Yulianti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article discusses how schools in Indonesia combine international and national curricula. This study was conducted through the systematic literature review (SLR) method which was analyzed using Paulo Freire's critical pedagogy framework. Based on 18 articles that have met the inclusion criteria, the adoption of international curricula, such as Cambridge or the International Islamic Boarding School (IIBS) is carried out by adjustment and negotiation that combines global standards with local cultural values, religion, and national identity based on Pancasila. The findings show that there is a pedagogical shift from traditional models to collaborative learning that is dialogical, project-based, and the use of technology, thus opening up the space for co-creation of knowledge as stated by Freire. This study confirms that curriculum hybridization can be a means of humanization when global and local knowledge can be placed equally and equitably. However, the implementation of the hybrid curriculum poses challenges in the form of access inequality due to differences in economic ability, geographical location, and school characteristics. The study also emphasizes the importance of education policies that ensure equitable distribution of service quality, strengthening teacher competencies, and curriculum design that allows for reflective dialogue between global contexts and cultural values and national identity.